The effect of walking sounds from different walked-on materials on the soundscape of urban parks - Aletta, Francesco; Kang, Jian; Fuda, Samuele; Astolfi, Arianna (Journal of Environmental Engineering and Landscape Management, 2016)
Urban parks are essential environmental resources in contemporary cities, for the substantial social and psychological relief they provide for local communities. In recent years, the potential of the soundscape approach for enhancing the ecological contribution of such environmental assets has been intensely investigated. Although, researchers tended to focus on the perception of people “staying” in the park, whilst it is important to consider how the sonic environment would be dynamically perceived by users walking across the park. Within this framework, the present study aimed to investigate the effect of different footpath materials on soundscape quality and walking quality perception for people walking in an urban park, considering that the experience of such users is affected by both the background acoustic environment of the park and their walking sound. To this purpose, a laboratory experiment was carried out with 25 participants. Four different walked-on materials that are likely to be used in urban parks were tested: grass, wood, stone and gravel. Results show that the material factor has a significant effect on both auditory and haptic perception. Furthermore, positive correlations can be observed between auditory and haptic variables, confirming that the soundscape appreciation for people walking in urban parks is likely to be affected also by other but aural sensory modalities. The paper ultimately points out that it is possible to re-think the approach to urban parks design and more specifically to the footpaths and the walking sounds that their materials are likely to produce.